Deconstructing innercirclism: a critical exploration of multimodal discourse in an English as a foreign language textbook. Issue 1 (2nd January 2023) - Smith, Christopher
ABSTRACT: English as a foreign language (EFL) teachers and students are often pressured to use generic, globally published textbooks featuring 'inner-circle' social realities. While some studies look at specific instances of content that socially marginalizes their intended audiences, few attempt comprehensive examinations of the multimodal ensembles on each opened page. Inspired by critical discourse studies that problematize some textbooks as vehicles for social injustice, this study features a novel, critical multimodal analysis process (CMAP) to look closer at the discourse in a popular textbook, asking: (1) What power relations and ideologies are harbored in the multimodal discourse? (2) What dominant narratives do the lessons appear to teach? After analyzing six units of lessons in a popular, globally published EFL textbook, CMAP reveals dominant inner-circle perspectives and othering, to which this study collectively labels innercirclism . Considering globally published EFL textbooks continue to be a popular choice for academic programs in expanding circle nations, the implications of this study suggest innercirclism diminishes the pedagogical vision of the teacher to ensure the value of their students' investment in English language learning.